CURRENT ISSUES ON JOB STRESS IN JAPAN AND WORKSITE MENTAL HEALTH APPLICATION AMONG JAPANESE COMPANY A Case Study Analysis - Purnawati, S. (BALI MEDICAL JOURNAL, 2013)
Background: Issues about job stress is more popular in the world currently. Not just for Japan, Korea and Taiwan, but also an important issue in EU countries, especially the UK and Finland Increase of awareness about job stress effects on work performance, productivity and mental health is as one reason of the phenomenon. Objective: The present study aimed to explore the issue of job stress in Japan for the reference of good practices to Indonesia. Methods: This study, based on observational studies in the period of September-December in year 2010 in Tokyo, Kawasaki and Kitakyushu Japan. Observations on Japanese Company and discussions with experts, such as: occupational physician of Riken Company, experts from:  Tokyo University and Tokyo University’s occupational physician, Department of ergonomics, the Institute of Industrial Ecological Sciences UOEH (University of Occupational and Environmental Health), Institute for Science of Labor, and researcher of Japan NIOSH. Two stress management training and occupational mental health’ application program were observed in the period of October-December. Result: The trend of current occupational mental health research in Japan has being moved from job stress to more advanced issues of work engagement and work-life balance. There are three approaches to prevention of job stress. Considering the three approach could improve of worker productivity and well-being. The training for Tokyo University’s staffs was as one session of individual-oriented stress prevention approach. It was conducted in very interactive class lecture. During 2 hours session, the participants learned some knowledge about job stress and its risk factors, exercised to construct better cognitive for stress prevention and productivity, practiced of progressive muscle relaxation technique, group work, did some home works and filled an evaluation sheet after the session was finish. We also observed the occupational mental health program at Riken Company that was covered of primary, secondary and tertiary prevention of occupational mental health program of workers mostly on job stress issue. Conclusion: It was concluded that although many efforts has made to anticipate the problem of job stress in Japan, it is still need further studies to find the most appropriate instruments for the indicator of job stress and methods of intervention which are most effective for employees and company, as well as general improvement for well-being of workers and their family as they are a part of community.